Strategies of Students with Mental Illness in Completing Education at Universitas Maritim Raja Ali Haji - Nurfinahati; Sri Wahyuni; Rahma Syafitri (Indonesian Journal of Medical Anthropology, 2023)
Â  Mental illness is a disease that affects mood, thinking, and behavior. Mental illness is recognized as hindering students from completing their education. The pressure and burden from parents that require their children to finish quickly becomes a mental disorder in itself. Therefore, the purpose of this study is to provide an overview of how Raja Ali Haji Maritime University students can survive completing their education in conditions of mental health disorders or mental illness. Using descriptive and qualitative methods, interviews were conducted to obtain the required data. Next in the analysis is the theory of social capital. The results of this study have a pattern of strategy in which it shows a social network in the form of creating trust, reciprocal relationships, and the existence of values and norms that are built in the process of completing education